The use of a shared database for cost reduction with user licenses: An experience report - Conde Junior, Carlos C. S.; Correa, Marcus V. C.; Barbosa, Hualter Oliveira; Silva, Tatiany Mafra da (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2024: Anais do XXVII Congresso Ibero-Americano em Engenharia de Software, 2024)
This article presents an experience report that analyzes the migration of servers to the data center as a solution to reduce financial costs and improve the performance and usability of the Jira tool. The solution adopted by the team resulted in a 70% reduction in costs compared to the option of maintaining the old data process and servers provided by Atlassian. Such works reinforce the need for companies to rethink traditional models, always aiming to reduce costs and process risks. Solutions from research and development (R&D) projects can play an important role in evaluating and testing possible changes in the process without compromising or interrupting production.